The Extraction of Zingiber Officinale Rosc as a Natural Insecticide for Aedes Aegypti Larvae - Boekoesoe, Lintje; Ahmad, Zul Fikar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Dengue fever is a health problem in Indonesia, including in Gorontalo Province, with an incidence rate of 101.53 per 100,000 population. One of the efforts to prevent the incidence of dengue fever is the use of natural insecticides, including red ginger. This study aims to assess the effectiveness of red ginger juice on the mortality of Aedes aegypti mosquito larvae. This research took place at the Laboratory of the Department of Public Health, the State University of Gorontalo, in 2021 using a True Experiment design. The mosquito larvae samples used were 500 larvae of Aedes aegypti instar IV mosquitoes taken from endemic areas of dengue fever in Gorontalo. Data were analyzed using the One Way ANOVA statistical test. Red ginger extract was given in five concentrations, namely 60%, 70%, 80%, 90%, and 100%. The results showed an effect of red ginger extract on the mortality of Aedes aegypti mosquito larvae at each treatment concentration given (p-Value = 0.000). The higher the concentration level given, the higher the larval mortality rate will also be. Red ginger is expected to be used by the community to prevent dengue fever.